Lesbian and working relationship: analysis of the insertion in the labor market - Santos, Dávila Cristina dos; Cassandre, Marcio Pascoal (Revista Hipótese, 2016)
The purpose of this article is to know about how sexual orientation interferes with the hiring of lesbian workers in the city of Maringa, so that eleven female workers were interviewed. Their reports were treated by the testimonio as a strategy in the life history. The consonance between sex and gender is in the daily lives of these female workers, and the performative acts considered "feminine" constitute themselves necessary at the time of contracting and during their stay in the company.
Keywords: Female workers; Gender; Lesbians; Heteronormativity